Validação de conteúdo do diagnóstico de enfermagem padrão ineficaz de alimentação do lactente - Diniz, Camila Maciel (2017)
The practice of nursing has been gaining subsidies for its improvement and one of the tools used for this is the performance of diagnostic validation studies, sustained on a consistent theoretical basis. Thus, the present study has as objective to verify the validity of the structure of the nursing diagnosis Ineffective Infant Feeding Pattern (IIFP) by performing two steps, namely: construction of a middle range theory (MRT) and content analysis by judges. The first stage of the study, carried out from March 2016 to July 2017, was carried out through a broad search in the literature, with the aid of the following descriptors: feeding patterns, infant nutrition disorders, deglutition disorders, sucking behavior, infant, feeding behavior, feeding and eating disorders of childhood and nutrition disorders from the Medline, Lilacs and Scopus databases. It is emphasized that the studies listed from the above descriptors triggered new searches through their references. At the end, 60 studies were selected. MRT allowed the identification of 12 etiological factors for the occurrence of IIFP and 13 clinical indicators. Of these results, five factors were already part of the NANDA-I structure. All clinical indicators listed were identified by MRT. The findings of the first stage were submitted to content analysis by nurse judges, constituting the second stage of the study, conducted between August and November 2017. The sample of this stage consisted of 23 judges. A content validity index (CVI) of 0.9 was adopted for adequacy of the evaluated item. The Wilcoxon test was used to obtain these values. Of the 12 etiologic factors, Oropharyngeal deformity, inadequate food supply pattern, Gastroesophageal reflux, Unsatisfactory suction mechanisms, Seizure episodes, Prolonged use of enteral probes and Prematurity were validated by the judges. Regarding clinical indicators, with the exception of impaired skin and mucous coloration, all other indicators had their content validated. For the elements that did not reach the expected CVI, changes were made as suggested by the judges. The findings of the present study confirm the structural inconsistency pertinent to the IIFP diagnosis brought by the NANDA-I taxonomy, emphasizing the need for diagnostic validation in the three aspects - theoretical validation, content validation and clinical validation. Thus, it is suggested that the results of this study be submitted to clinical validation in a specific population.